(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article examines the basic principles of creating beauty from the plant world. It also examines, from the point of view of an art historian, the methods of creating works of art from ornamental plants, and the role of future specialists - landscape designers - in creating gardens and parks.